Increasing the use of mobile technology-derived endpoints in clinical trials. - Herrington, W; Goldsack, J; Landray, M (SAGE Publications, 2018)
Mobile technology can be used in clinical trials to generate novel endpoints that provide information that was previously difficult or impossible to obtain. Technology-derived novel endpoints could also make clinical trials more efficient and less burdensome to trial participants while contributing to a meaningful and real-world understanding about patient experiences beyond the brief data "snapshots" typically gathered in clinical care or research settings. This research letter summarizes the recommendations provided by the Clinical Trials Transformation Initiative (CTTI) which are intended to support the selection, development and inclusion of such technology-derived novel endpoints in future clinical trials.